Pemanfaatan Artificial Intelligence dalam Perencanaan, Pelaksanaan, dan Evaluasi Pembelajaran oleh Mahasiswa Calon Guru Universitas Terbuka - Siswanto, Romi; Kusmawan, Udan; Sukmayadi, Dodi; Anwar Abidin, Achmad; Kadarisman (Program Studi Manajemen Pendidikan Islam, 2024)
This study aims to analyze the utilization of artificial intelligence (AI) in lesson planning, implementation, and assessment by pre-service teachers. The study used a mixed methods approach, involving 150 students through quantitative questionnaires and in-depth interviews with 15 students as the qualitative sample. The findings reveal that while students' knowledge of AI remains relatively low, there is a strong interest in further integrating AI into teaching practices. AI tools, such as ChatGPT and Canva, significantly assist students in drafting lesson plans, creating visual learning media, and designing interactive assessment tools. However, limited digital literacy and a lack of proper training present major challenges in AI adoption. This study recommends intensive AI training for pre-service teachers and suggests expanding the research to other study programs to understand variations in AI adoption.